High serum resistin levels correlate with the increased severity of psoriasis vulgaris - Tandyono, Venny; Oenatra, Dave Gerald; Sudarsa, Prima Sanjiwani Saraswati; Pramita, Nyoman Yoga Maya (Journal of Pakistan Association of Dermatologists, 2024)
Background Psoriasis is a chronic inflammatory skin disorder characterized by an increase in epidermal turnover and inflammation of the dermis. Resistin is one of the adipokines that promotes the production of proinflammatory mediators involved in the pathogenesis of psoriasis. This study aimed to assess the correlation between serum resistin levels with the severity of psoriasis vulgaris. Methods The disease severity was recorded based on Psoriasis Area and Severity Index (PASI) score, and serum resistin levels were obtained for each subject. The independent t test and One-Way ANOVA were applied for comparative analysis and the Pearson test was used to measure correlation analysis. Results Serum resistin levels didn’t differ significantly between men and women (p=0.998) or also between the normal, overweight and obese subjects (p=0.624). Serum resistin levels were significantly higher in subjects with psoriasis vulgaris compared with controls (p<0.001). High serum resistin levels were markedly correlated (r=0.848; p<0.001) with the increased severity of psoriasis vulgaris based on the Psoriasis Area Severity Index (PASI) scores. Conclusion Serum resistin levels mediates the degree of inflammation of psoriasis and correlates with the severity of psoriasis vulgaris.